Hello Folk: We Are Responsible for What We Will Face in 2025; Evidence from Philosophical Underpinnings of Social Capital (The Pakistan Development Review, 2016)
Social capital is a very important facet of society and has strong relevance to economic landscape of a country. There are different theories about the nature, accumulation, growth and validity of social capital as an instrument of economy. This paper explains the philosophical context of social capital and validate through a model using Berg, Dickhaut and McCabe trust game that we all transfer a set of values to our next generation, which ultimately manifest as social capital in the real world. The transferred values affects each agent‟ decision whether to trust other members of the society and participate in a socio-economic exchange or not. If he trusts, he reaps substantial gains from exchange, and ultimately social capital will be concreted. But if he does not, he will face a major loss and overall social capital will be dented. A distrustful ancestor will further induce agents to withdraw from the market and not to invest. This will lead a society to an overall mistrust paradigm and eventual downfall. On the other hand, the level of cooperation in the members of society increases as the good experience is transferred across generations. Economic impacts of social capital have been elucidated using Leonhard Euler function and Newton Leibniz integration processes. The ethical framework for society and role of literature in transfer of beliefs, values and culture from one generation to other has also been discussed at length. The paper is a unique study of how we all will be responsible for the kind of social capital will have in 2025. JEL Classification: D71, D72, Z11, Z12, Z13 Keywords: Social, Capital, Model, Transfer, Generations, Values, Trust, Beliefs, Cooperation, Ethics, Literature